Pregnancy and supplementation of vitamins and mineral compounds - Gawryszczak, Samanta; Górska, Justyna; Gliwa, Anna; Halczuk, Izabela; Stachura, Bartłomiej; Nowak, Katarzyna (Quality in Sport, 2024)
Introduction and purpose Proper nutrition and appropriately chosen supplementation during pregnancy significantly ensure a healthy pregnancy and fetal development. Both nutrient deficiencies and excesses can have negative health effects on both the mother and the child. This article discusses specific active substances that are particularly important in supplementation of pregnant women. The aim of the study is to describe the current state of knowledge about the importance of adequate supply of vitamins and minerals compounds during pregnancy, in order to increase women's awareness and encourage improvement in dietary habits. Material and methods of research For this study, a review of literature available on Google Scholar and PubMed was conducted. From the analysis, studies published before 2017 were excluded. State of knowledge Based on the current state of knowledge, we know that the nutrition of pregnant women undergoes partial modifications. To ensure a healthy pregnancy, there is an increased energy demand in the body, making appropriate weight gain crucial. Routine use of multivitamin supplements is not recommended for pregnant women, as a balanced diet should be the primary source of macronutrients, micronutrients, and vitamins. Key components that are used in supplementation for pregnant women in specific cases include iron, folic acid, vitamin D, DHA acids, and iodine. Conclusions This work emphasizes the significant impact of proper nutrition and appropriately selected supplementation in pregnant women on reducing the risk of various pregnancy complications and fetal developmental disorders. It highlights the importance of deficiencies and excesses of vitamins and minerals compounds in the diet of women during the preconception period, all trimesters of pregnancy and lactation.